Successful Long-Term Control of the Syndrome of Episodic Angioedema With Eosinophilia (Gleich Syndrome) With Low-Dose Imatinib Mesylate and Prednisone - Joseph H. Butterfield MD (SAGE Publishing, 2021)
The syndrome of episodic angioedema with eosinophilia, first reported over 40 years ago, is a hypereosinophilic disorder that, uniquely, is not associated with end-organ pathology. However, patients develop a constellation of symptoms that include angioedema, urticaria, fatigue, and fever. Episodes are accompanied by massive hypereosinophilia and weight gain. Type II serum cytokine levels (IL-5, IL-13, IL-9, and IL-10) show cyclic variations peaking at or just prior to the peak of eosinophilia and an abnormal Th2 cell phenotype has been reported. Attacks may occur with predictable regularity and have been described in both adults and children. Glucocorticoid therapy reliably reverses symptoms with accompanying diuresis, defervesce, and normalization of the eosinophil count. In this report, a patient who had the syndrome of episodic angioedema with eosinophilia exceeding 20 years is reported. He has had no end-organ damage to date. Testing for the CHIC 2 deletion, a surrogate for the FIP1L1-PDGFRA fusion, was negative. Use of imatinib mesylate, initially as a steroid-sparing agent, and subsequently as a maintenance medication, plus low-dose prednisone has provided long-term control of hypereosinophilia and all clinical manifestations.